Divergent Effects of the N-Methyl-D-Aspartate Receptor Antagonist Kynurenic Acid and the Synthetic Analog SZR-72 on Microcirculatory and Mitochondrial Dysfunction in Experimental Sepsis - Juhász, László; Rutai, Attila; Fejes, Roland; Tallósy, Szabolcs P.; Poles, Marietta Z.; Szabó, Andrea; Szatmári, István; Fülöp, Ferenc; Vécsei, László; Boros, Mihály; Kaszaki, József (Frontiers in Medicine, 2020)
Introduction: Sepsis is a dysregulated host response to infection with macro- and microhemodynamic deterioration. Kynurenic acid (KYNA) is a metabolite of the kynurenine pathway of tryptophan catabolism with pleiotropic cell-protective effects under pro-inflammatory conditions. Our aim was to investigate whether exogenously administered KYNA or the synthetic analogue SZR-72 affects the microcirculation and mitochondrial function in a clinically relevant rodent model of intraabdominal sepsis. Methods: Male Sprague–Dawley rats (n=8/group) were subjected to fecal peritonitis (0.6 g kg-1 feces ip) or a sham operation. Septic animals were treated with sterile saline or received ip KYNA or SZR-72 (160 µmol kg-1 each) 16h and 22h after induction. Invasive monitoring was performed on anesthetized animals to evaluate respiratory, cardiovascular, renal, hepatic and metabolic dysfunctions (PaO2/FiO2 ratio, mean arterial pressure, urea, AST/ALT ratio and lactate levels, respectively) based on the Rat Organ Failure Assessment (ROFA) score. The ratio of perfused vessels (PPV) of the ileal serosa was quantified with the intravital imaging technique. Complex I- and II-linked (CI; CII) oxidative phosphorylation capacities (OXPHOS) and mitochondrial membrane potential (ΔΨmt) were evaluated by High-Resolution FluoRespirometry (O2k, Oroboros, Austria) in liver biopsies. Plasma endothelin-1 (ET-1), IL-6, intestinal nitrotyrosine (NT) and xanthine oxidoreductase (XOR) activities were measured as inflammatory markers. Results: Sepsis was characterized by an increased ROFA score (5.3±1.3 vs 1.3±0.7), increased ET-1, IL-6, NT and XOR levels, and decreased serosal PPV (65±12% vs 87±7%), ΔΨmt and CI–CII-linked OXPHOS (73±16 vs 158±14, and 189±67 vs 328±81, respectively) as compared to controls. Both KYNA and SZR-72 reduced systemic inflammatory activation; KYNA treatment decreased serosal perfusion heterogeneity, restored PPV (85±11%) and complex II-linked OXPHOS (307±38), whereas SZR-72 improved both CI- and CII-linked OXPHOS (CI: 117±18; CII: 445±107) without effects on PPV 24h after sepsis induction. Conclusion: Treatment with SZR-72 directly modulates mitochondrial respiration, leading to improved conversion of ADP to ATP, while administration of KYNA restores microcirculatory dysfunction. The results suggest that microcirculatory and mitochondrial resuscitation with KYNA or the synthetic analogue SZR-72 might be an appropriate supportive tool in sepsis therapy.